Case Journal “Bronchopneumonia In Adult Patients” - Della Terulin Pinem; Khainir Khainir; Suandy Suandy (CV. AFDIFAL MAJU BERKAH, 2026)
Bronchopneumonia is a lower respiratory tract infection characterized by inflammation of the bronchioles and alveoli caused by microbial infection. It remains a significant cause of morbidity and mortality, particularly among older adults and individuals with underlying risk factors. This case journal aimed to describe the clinical manifestations, diagnostic approach, and management of bronchopneumonia in an adult patient. A case report method was employed using data obtained from medical records, including history taking, physical examination, laboratory investigations, radiological findings, and therapeutic evaluation during hospitalization. A 58-year-old male presented with shortness of breath, productive cough with yellowish sputum, fever, and chest pain during coughing. Physical examination revealed tachypnea, coarse crackles, increased tactile fremitus, and dullness to percussion over the right lower lung field. Laboratory investigations demonstrated leukocytosis and elevated C-reactive protein levels, while chest radiography showed multiple patchy infiltrates in both lower lung fields. The patient was diagnosed with bronchopneumonia and treated with antibiotics, oxygen supplementation, mucolytic therapy, and supportive management. Accurate diagnosis and appropriate management contributed to clinical improvement and reduced the risk of complications associated with bronchopneumonia.